2007
DOI: 10.1007/s10067-007-0642-x
|View full text |Cite
|
Sign up to set email alerts
|

Sick leave and work disability in patients with early arthritis

Abstract: We studied the occurrence of sick leave and work disability, the presence of workplace adaptations and the usage of professional guidance related to working problems in patients with early arthritis. Inclusion criteria were arthritis symptoms of less than 2 years duration and a paid job at the time of diagnosis. Assessments were done in connection with an early arthritis clinic (EAC) at entry into the cohort and 12 months thereafter by means of a questionnaire comprising questions on sick leave (absenteeism fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 30 publications
4
32
1
Order By: Relevance
“…Similarly, in a longer period of 12 months, Zirkzee et al (15) described sick leave for Ͼ2 weeks in 41% of patients with early arthritis. Sick leave was also more frequently observed among workers with arthritis and related joint disorders than in a comparison group in the US (32).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, in a longer period of 12 months, Zirkzee et al (15) described sick leave for Ͼ2 weeks in 41% of patients with early arthritis. Sick leave was also more frequently observed among workers with arthritis and related joint disorders than in a comparison group in the US (32).…”
Section: Discussionmentioning
confidence: 89%
“…Patients selected for biological therapy during the first years had usually been on sick leave for a long time and this might reflect that patients with severe disease and disability had limited success in returning to work (23). Previous data on working capacity after introduction of biological treatment are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2,[4][5][6][7][8][9][10] Earlier studies suggested that the majority of AS patients did not experience work disability, but more recent studies concluded that work disability in AS appeared worthy of increased attention. [3][4][5]11] Ankylosing spondylitis and RA are chronic disabling conditions having a socioeconomic impact on family and society. One would expect to know which diseases have more of an impact on socioeconomic consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Although AS and RA both influence quality of life and work status, there are only a few studies comparing the work status and related determinants between these two rheumatic conditions. [5,11,12] The aim of this study was to determine and compare the work status in patients with RA and AS and also to define the related factors on work disability in these patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation